Enhancing Islamic Moderation in Pesantren: The Role of Kiai Exemplary, Curriculum, and Santri Activities - Akmansyah, Muhammad; Nurnazli, Nurnazli (Mafapress - Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA Pati, 2024)
This research aims to examine the strengthening of Islamic moderation through the exemplary role of Kiai, the educational curriculum, and the daily activities of Santri. Through a qualitative approach, the research was conducted on three Pesantren in Bandar Lampung. Data were collected through interviews, observations, and documentation. The analysis follows the procedure of data reduction, data presentation, and conclusion drawing. The results showed that Kiai as a role model in strengthening Islamic moderation through various approaches, namely emphasizing Ahl al-Sunnah wa al-Jamâ'ah and participatory leadership; integrating spiritual practices with social engagement; and focusing on a balanced interpretation of the Qur'an by emphasizing justice, knowledge, and discipline. Assalafi al-'Aafiyah's curriculum prioritizes traditional methodology and respects multiple interpretations; Al-Hikmah combines traditional with modern teachings; and Darul Hidayah emphasizes character development and ethics in addition to memorizing the Qur'an. Santri's daily routines reflect different approaches, with Assalafi al-'Aafiyah focusing on a structured schedule of activities and community service, Al-Hikmah integrating formal education with community rituals, and Darul Hidayah prioritizing ethical development. This research calls on policy makers to increase support for strengthening Islamic moderation in pesantren.